2022
DOI: 10.1371/journal.pone.0277513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the poultry red mite (Dermanyssus gallinae) load on the plumage condition in commercial laying hen farms

Abstract: Plumage damage (PD) resulting from severe feather pecking (SFP) is a significant problem for animal welfare, performance, and economics in commercial laying hen farms. Genetics, nutrition, and housing conditions are central complexes that contribute to the multifactorial cause of SFP. Practical experience suggests that infestation by the poultry red mite (PRM), which is the most severe ectoparasite of laying hens in cage-free housing systems, may be a risk factor for the occurrence of PD, although evidence-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Self-assessed infestation rates on commercial laying hen farms differ from mite trap-based infestation rates ( Waap et al, 2019 ), resulting in underestimation of infestation load. Schreiter et al (2022) identified PRM load as a risk factor for severe FP. In our study, FP was appointed as the most relevant health and welfare problem in hens housed in aviaries by poultry experts.…”
Section: Discussionmentioning
confidence: 99%
“…Self-assessed infestation rates on commercial laying hen farms differ from mite trap-based infestation rates ( Waap et al, 2019 ), resulting in underestimation of infestation load. Schreiter et al (2022) identified PRM load as a risk factor for severe FP. In our study, FP was appointed as the most relevant health and welfare problem in hens housed in aviaries by poultry experts.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically for industrial poultry houses using enriched cages, stacking them on top of each other, and creating multiple floors, the traps were placed on different rows (sides to middle) and floor levels (high, medium, low) at equal distances from one another, beginning from the entryway until the opposite side. Placement spots included perches, particularly the higher ones in aviary systems, under the egg conveyor belt, metal connections, under feeders, under watering lines, and grates/slats in or near nests in backyard poultry farms [ 5 , 27 , 31 , 35 ]. The traps were secured using ten black cable ties (thickness of 2 mm, length of 200 mm), which accompanied each set of 10 traps.…”
Section: Methodsmentioning
confidence: 99%